Alternatif Penanganan Masalah Stabilitas Tanah Pada Lereng Galian Proyek Jalan Tol Padang - Sicincin - Herlambang, Tomy; Budisatria Mochtar, Indrasurya; Rendy Satrya, Trihanyndio (Syntax Corporation, 2025)
The Padang–Sicincin Toll Road Construction Project is part of the supporting corridor of the Trans-Sumatra Toll Road, with cut sections at STA 26+825 – 27+400 and STA 28+900 having heights of approximately ±18 meters and ±21 meters. Due to site conditions, ideal slope angles could not be applied, necessitating slope reinforcement using soil nailing based on the design documents. In several locations, cracks appeared on the slopes, creating new issues that require appropriate alternative solutions. The conducted analyses include crack cause analysis, slope stability analysis, and determination of field-based solutions. Slope stability was analyzed at four different locations under conventional (uncracked) and cracked conditions using Slope/W software. The crack cause analysis was carried out through literature studies and field observations. Solutions for the field problems were based on the results of slope stability and crack cause analyses. The analysis results showed that the cracked condition was the most critical compared to the conventional condition, indicated by a decrease in the safety factor and an increase in the depth of the slip surface. The cracks were caused by rainfall leading to soil particle detachment, erosion-prone soil types, and the absence of vegetation cover. The proposed alternative solutions include the use of diversion channels to capture rainwater and prevent surface flow on the slopes, anchors to improve slope stability, geosynthetics to create an impermeable layer on the slope, and drainage wells. It can be concluded that the cut slopes are unstable under both conventional and cracked conditions, with the cracks being caused by erosive agents, soil erodibility, and lack of surface cover. The proposed erosion control alternatives include side channels, anchors, geosynthetics, and drainage wells.